Integrative Learning in Islamic Indonesian EFL Classroom: Challenges and Opportunities - Anggarini, Ida Fitri; Azzahwa, Amanda Cyntia Afifatuz Zahro; Setyawan, Cacha Andana Dea; A'la, Muhammad Tibyan Rofiqul; Maghfiroh, Alfi Lailatul; Putri, Rahma Henis Eka (Journal of English Teaching and Learning Issues, 2022)
Nowadays, several education approaches exist in this smart society 5.0 era, specifically in English language teaching. One of them is the integrative learning approach which means the process of making connections among concepts, experiences, and subjects. This study aimed to explore the integrative learning approach, challenges, and opportunities in Indonesian Islamic EFL classes. This study was held in a research class at Islamic Senior High School in Malang. This qualitative field research used observation, in-depth interviews, and documentation to collect primary data from five EFL students and one EFL teacher. The result shows that an integrative learning approach is needed; this class integrates both EFL and Islamic values because they must implement the values of Islam in their daily life. In addition, some of the challenges include difficulty translating from Arabic to English, pronunciation, and soon. On the other hand, this class also found that tajweed makes it easier to read English text by comparing maharijul huruf and its phonology. Also, mastering this integrative class makes it easier to find Islamic literature in the English language. Thus, this study significantly gave EFL teachers insights into implementing the integration between English language skills and Islamic teaching in the EFL classroom.